Development of millealab-assisted class of dynamic fluid in pbl-steam learning to improve students’ problem-solving skills in dynamic fluid material - Irgi Aditya; Parno; Sujito; Puji Hariati Winingsih; Muhammad Abd. Hadi Bin Bunyamin (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2025)
In the 21st century, the integration of essential skills commonly referred to as the 4Cs (critical thinking, communication, collaboration, and creativity) into science education has become imperative. Among these, problem-solving skills are central to fostering critical thinking and creativity. However, students' problem-solving performance in dynamic fluid concepts remains considerably low. This study aims to develop and evaluate the validity, practicality, and effectiveness of a MilleaLab-assisted virtual reality (VR) learning medium integrated with the Problem-Based Learning and STEAM (PBL-STEAM) approach to enhance students’ problem-solving skills in dynamic fluid materials. Employing a 4D research and development model (Define, Design, Develop, Disseminate), the media were assessed through expert validation questionnaires, student response surveys, classroom observations, and pre-and post-test problem-solving assessments. This study used a quasi-experiment pre-test post-test non-equivalent group design. There were 56 eleventh-grade students who divided into an experimental class and a control class, and were chosen Where the research subjects are selected based on the considerations of the subject teacher and the characteristics of both academic potential and student involvement potential in learning. Quantitative data were analyzed using descriptive statistics, t-tests, and normalized gain (N-Gain) calculations. Results indicated that the developed media was highly valid and practical, and significantly improved problem-solving skills, with an N-Gain of 0.85 in the experimental group compared to 0.68 in the control group. The novelty of this study lies in the integration of immersive VR-based learning using MilleaLab within the PBL-STEAM model on a complex physics topic, that has not been widely explored. Future studies are encouraged to implement this media across varied physic topics and over longer instructional periods to optimize its long-term impact on students’ problem-solving skills.